Efectos de inductores de resistencia sobre enfermedades foliares en el cultivo de arroz de secano favorecido en la zona de CEDEGE, Babahoyo - Yánez Zambrano, Omar Orlando (2025)
Rice (Oryza sativa) is one of the most important cereals in human nutrition. Diseases are among the most important limiting factors of productivity; these organisms are responsible for 37% to 50% of reported losses. Rice production in Ecuador is planted in Guayas and Los Ríos, both representing 83% of the national total. The most efficient strategy for rice producers to reduce losses caused by diseases consists of the application of fungicides. In this sense, the application of products that generate defense responses in plants helps the crop to control and prevent limiting diseases; so, finding control alternatives is ideal. This research aims to evaluate the effect of resistance inducers on foliar diseases in rice cultivation in the Babahoyo area. For this purpose, the FL-01 variety was planted in the field, in an experimental design of “Random Complete Blocks”, with eight (8) treatments, divided into three (3) repetitions. The comparison of the means in the treatments will be done with the Scheffé test at 1%. The products were: Salicylic Acid, Chitosan and Poly-Glucosarin in different doses, plus a control. The variables evaluated were related to production and incidence of diseases. The evaluations showed a reduction in the severity of damage (formula and diagrammatic table) with the application of salicylic acid and chitosan at a dose of 1.5 l/ha, 70% less compared to the control. In the case of incidence, this was lower with the application of salicylic acid and chitosan at a dose of 1.5 l/ha, with 72% less compared to the control. The application of Chitosan 1.5 l/ha (7850.0 kg/ha) and salicylic acid 1.5 l/ha (7843.33 kg/ha) presented the highest yields, with a lower value in the control (4803.33 kg/ha).